Copper-doped TiO2 photocatalysts: application to drinking water by humic matter degradation - Turkten, Nazli; Cinar, Zekiye; Tomruk, Ayse; Bekbolet, Miray (SPRINGER HEIDELBERG, 2019)
The aim of this study was to determine the photocatalytic performance of copper-doped TiO2 (Cu-TiO2) specimens on the degradation of dissolved organic matter (DOM) represented by a model humic acid (HA). TiO2 was synthesized by sol-gel method from an alkoxide precursor. Cu-doped TiO2 specimens containing 0.25 wt% and 0.50 wt% Cu were prepared by wet impregnation method using sol-gel synthesized as well as bare TiO2 P-25 and characterized by XRD, SEM, XPS, Raman spectroscopy, UV-DRS, and BET measurements. Their photocatalytic activities were evaluated with regard to degradation kinetics of HA in terms of UV-vis and fluorescence spectroscopic parameters and organic contents. HA fluorescence excitation emission matrix (EEM) contour plots indicated that the solar photocatalytic degradation pathway was TiO2-type specific and Cu dopant content.
Keywords: Cu-doped TiO2; EEM; Humic acid; Photocatalysis; Sol-gel; TiO2; DISSOLVED ORGANIC-MATTER; VISIBLE-LIGHT; METHYLENE-BLUE; CU; NANOPARTICLES; ANATASE; DECOLORIZATION; DISINFECTION; PERFORMANCE; ACID; Environmental Sciences & Ecology